Pengaruh Pemberian Ekstrak Etanol Bit Merah (Beta vulgaris L.) Terhadap Kerusakan Histologis Sel Hepar Mencit (Mus musculus) yang Diinduksi Parasetamol - Debora Marga Pangestika; . Suyatmi; Yulia Sari (Nexus Biomedika, 2013)
Background: Red beet (Beta vulgaris L.) has various components such as betalain, flavonoid, phenolic, ?-karoten, vitamin C and E, Fe, Zn, Cu, Mn, and Selenium. These components are potent to be antioxidant to protect liver from free radicals. The aims of this research were to evaluate hepatoprotective effect of ethanol extract of red beets on histologic damage of mices liver cells induced by paracetamol and the dose dependent of this extract. Methods: This was laboratory experimental research with the posttest only controlled group design. The subjects of this reaseach were 30 Swiss webster male mice (Mus musculus), 2-3 months old and 20 grams of weight, divided into 5 groups randomly. The groups were KK(-), KK(+), KP1, KP2, and KP3. Aquadest was administered to KK(-) and KK(+). Paracetamol was administered to KK(+), KP1, KP2, and KP3 on the day 12, 13 and 14. Red beet extracts were administered to KP1, KP2, and KP3 in dose 5.6 mg, 11.2 mg and 22.4 mg per 20 g BW of mice, successively. The hepatoprotective effects were assessed by counting the number of damage cells among 100 hepatocytes at central lobe zone of liver. Results: The result of One-Way ANOVA p = 0.000 (p < 0.05) showed a significant difference among each other group. The linear regression test p = 0.000 (p < 0.05) showed a correlation between increasing dosage and improving protective effect on mices liver cell damage. Conclusions: The ethanol extract of red beet had protective effect on histologic damage of mices liver cells induced by paracetamol. The increasing dosage of the red beet extract improved the protective effect to liver cells. Keywords : ethanol extract red beet, mice liver cells, paracetamol